Analysis of Dialysate pH and Temperature Stability on Hemodialysis Machines Using Internet of Thing Technology - P, Noviyanto Putera; Lusiana, Lusiana; Setioningsih, Endang Dian; Luthfiyah, Sari; Pati, Abhilash (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Therapy for kidney replacement with hemodialysis is a treatment that is carried out in patients with Chronic Kidney Failure to survive. Related to this matter, this study was done aiming to determine the stability of the dialysate fluid in the hemodialysis machine by measuring the temperature using the DS18B20 sensor and measuring the dialysate pH using the 4502C sensor on pre- and post-hemodialysis. Meanwhile, the research method and the manufacture of this module applied a pre-experimental research design with the independent variables involved are pH value and Dialysate Temperature, while the dependent variables are pH and Temperature Sensor. Furthermore, the control variable is the Traceable Tool. This research made a module using an Esp32 microcontroller system with an LCD that can be monitored using Android via the Internet of Things (IoT) system. In this case, the comparison of the results of the dialysate temperature values ​​during pre and post-obtained the maximum measurement error of 0.2%. Based on the measurement and data analysis, it can be concluded that there was no effect of pH and temperature values ​​during pre and post hemodialysis.